A alma e a morte na apologia do Fédon: Sócrates entre θάνατος e τεθνάναι - Vella, Giovanni (2019)
If Socrates’ death can be considered the capital event of Plato’s philosophizing, the goal of this investigation is to philosophically enhance the representation of this event which is seen in Phaedo’s apology, a dialogue depicted in Athens’s cell that describes the philosopher’s speeches and attitude “towards death” (πρὸ τοῦ θανάτου: 57a), on the last day of his life. Special attention is given to the textual signals as well as the argumentative steps of the single, coherent dialectical investigation which begins as of the apology (from 63b to 69e), attempting to question the reasons for Socrates’ atypical happiness towards death; the investigation follows after the apology (from 70 a to 107 b), accomplishing what had previously been achieved through a new, even more comprehensive philosophical foundation, whose object will be the immortality of the soul. Taking into account that there is evidence of a sole dialectical investigation which merges apology and Phaedo’s remaining part, the proemium and its representation will be read as the necessary theoretical step that introduces the sequence of arguments on the immortality of the soul, justifying the logical nature of their conclusions. By taking a precise reconstruction of the logical sequence that connects “death as an event” (θάνατος) to death as a “dead state condition” (τεθνανάι) in the central definition of 64 c, we welcome the hypothesis that, in the platonic proposition, the philosopher’s condition of “being dead” goes beyond the feasible objective of an ethical attitude proposed by Plato: according to some specialists, this would be a “living death” metaphor encompassed in the Greek term, the perfect death state to which each human existence is bound , as its necessary teleological orientation. Therefore, it is not a metaphor, but a real experience which death as an event – θάνατος – decided by the gods, simply enhances, promptly materializing the human being in each individual. Thus, in Phaedo the authentic platonic doctrine of knowledge and its realization in the investigation on the immortality of the soul is understood from the point of view of a unique anthropological contemplation of death, the event which allows for – when wisely understood, and not feared as the worst of all evils – the contemplation of – even in its most decisive instant – the soul and its immortal move, in other words, its strength and intelligence, which reveals its own sovereign autonomy and reasoning prior to and beyond the body